2007
DOI: 10.1002/jqs.1027
|View full text |Cite
|
Sign up to set email alerts
|

Late Quaternary environments, vegetation and agriculture in northern New Zealand

Abstract: A sedimentological and plant microfossil history of the Late Quaternary is preserved in two sediment cores from early Polynesian ditch systems on southern Aupouri Peninsula. The study places human activities into a geomorphological and ecological context and allows comparison of natural and anthropogenic effects on two different geological settings: a floodplain and a relatively closed peat swamp. The data fill part of the current gap in the environmental record from northern New Zealand, namely MIS 3 (57k-26k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…in our study, glacial Agathis spp. experienced warmer and wetter conditions during the last glacial period compared with modern climates (Elliot et al, 2005;Horrocks et al, 2007;D'Costa et al, 2008). We examined the effects of increasing [CO 2 ] in controlled locations in both study systems; the full Juniperus spp.…”
Section: Box 1: Case Study Testing the Set-point Hypothesis For C I /C Amentioning
confidence: 99%
“…in our study, glacial Agathis spp. experienced warmer and wetter conditions during the last glacial period compared with modern climates (Elliot et al, 2005;Horrocks et al, 2007;D'Costa et al, 2008). We examined the effects of increasing [CO 2 ] in controlled locations in both study systems; the full Juniperus spp.…”
Section: Box 1: Case Study Testing the Set-point Hypothesis For C I /C Amentioning
confidence: 99%
“…Humans have likely impacted Australian wetland ecosystems for the entire duration of the Holocene (Fletcher and Thomas, 2010b;Black et al, 2007), and an impact has been recognised in New Zealand during the last millennium (Horrocks et al, 2007;McGlone and Wilmshurst, 1999b). This anthropogenic influence has intensified across Australasia since the arrival of European settlers Bickford and Gell, 2005;McGlone and Wilmshurst, 1999a), which may lead to palaeolimnological signals unrelated to climate.…”
Section: Lakes Wetlands and Peatlandsmentioning
confidence: 99%
“…If this is the case, then the MIS 3 forest may be coeval with the forest represented by the plunging branch and peg roots in unit 2 of Johnston's Gum Hole. Horrocks et al (2007) have also recently reported evidence for Agathis forest early in MIS 3 from nearby Motutangi Swamp. Late glacial records from Kaitaia Bog and nearby Lake Tangonge indicate that Fuscospora forest, similar to that reported here for MIS 4, occurred during MIS 2 in the Far North (Elliot, 1998;Elliot et al, 2005).…”
Section: Palaeoenvironments Of Johnston's Gum Holementioning
confidence: 78%
“…The Gum Hole, and similar alternating sand/peat sequences on coastal dunes in Northland Horrocks et al, 2007), represent an important repository of proxy-climatic information for the late Quaternary. The shallow seas on both sides of the Aupouri Peninsula imply major shifts in hydrology and sediment supply with relatively slight changes of sea level.…”
Section: Discussionmentioning
confidence: 99%